2004
DOI: 10.1080/02841850410003798
|View full text |Cite
|
Sign up to set email alerts
|

Dermoid tumor with involvement of the frontal lobes

Abstract: Intraparenchymal location of a dermoid tumor is extremely rare, and there are only four reports in the literature. This article presents a patient with a dermoid tumor with trilobulated components; an extra-axial component in the basal frontal/ethmoidal region, and two intra-axial components located in each frontal lobe. In addition, two small fat-density lesions anterior to the component in the left frontal lobe were present, probably due to partial intraparenchymal rupture of the tumor. The pathogenesis of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…10 Their occurrence inside the brain parenchyma is not commonly encountered. 8,9,24,29 In a recent review of all intraaxial dermoid cysts, the authors found only 4 cases of frontal dermoid cysts, emphasizing the novelty of our case. 8,20,24,29 Since gross-total resection is the mainstay of treatment for both of these lesions, 4,7 the patient in our case underwent resection of both lesions via the pterional approach.…”
Section: Discussionmentioning
confidence: 99%
“…10 Their occurrence inside the brain parenchyma is not commonly encountered. 8,9,24,29 In a recent review of all intraaxial dermoid cysts, the authors found only 4 cases of frontal dermoid cysts, emphasizing the novelty of our case. 8,20,24,29 Since gross-total resection is the mainstay of treatment for both of these lesions, 4,7 the patient in our case underwent resection of both lesions via the pterional approach.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 8 cases of intraaxial dermoid cysts have been reported in the literature, with 2 of these lesions being found in the brainstem. 3,8,9,14,16,20,22,23 We report the first case of an intraaxial dermoid cyst located in the medulla and review the literature of the existing intraparenchymal cases.…”
mentioning
confidence: 99%